Kualitas Kerabang Telur pada Berbagai Itik Petelur Lokal di Balai Pembibitan dan Budidaya Ternak Non Ruminansia (BPBTNR), Ambarawa - Eka Fitriani; Sri Isdadiyanto; Silvana Tana (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Duck (Anas platyrhynchos) was one type of potential poultry producing eggs. Efforts to increase productivity can be done through the selection of good breeding stock, provision of adequate food in quantity and quality as well as the provision of additional feed (feed additive). Calcium carbonate was a mineral needed by a group of ducks for egg shell formation. The purpose of the research was quality of the local duck eggs Pengging include ducks, duck Tegal and duck Magelang based on the quality of its shell. This study uses a completely randomized design (CRD) with three treatments (Pengging duck, duck Ducks Tegal and Magelang) and 6 replication.The measured variable was the index of egg shell, eggshell weight, eggshell thickness and eggshell calcium. Data were analyzed using Analysis of Variance (ANOVA) with a differentiating factor is the type of duck. Real different data analyzeda further test using Least Significant Differences Test (LSDT) at the level of 95%. The results of this research indexshowed that ducks Tegaland duck Pengging no significant difference but significantly different with Magelang ducks. Weight eggshell and eggshell thickness showed no significantly different for the three types of local ducks. Eggshell calcium levels showed that Magelang ducks and duck Pengging no significant difference but significantly different with Tegal ducks.Conclusion of the study was index eggshell and eggshell calcium could affect the quality of the eggshell. Keywords: Local Ducks in Central Java, the index of egg shell, eggshell weight, eggshell thickness, eggshell calcium.